High pressures depress the onset of intracellular vitrification - Stewart Gault; Charles S. Cockell (PLoS ONE, 2025)
The low temperature limit for life remains elusive and poorly understood. This ignorance is further compounded when applied to life in multi-extreme environments where low temperatures combine with factors such as high salt concentrations, or high environmental pressures. It has been proposed that the onset of intracellular vitrification enforces a biophysical low temperature limit for unicellular life at ~ −23 °C. However, it has not been demonstrated how high-pressures affect intracellular vitrification, which is vital for understanding the habitability of low temperature, subsurface environments, both on Earth and on other planetary bodies. Here, we used high-pressure differential scanning calorimetry to measure the intracellular vitrification of Bacillus subtilis across pressures ranging from 1 to 1000 bar. We find that high pressures depress the onset of intracellular vitrification in a pressure dependent manner, which is tightly correlated with the ability of pressure to depress the freezing point of water. Additionally, we show that sub-molar concentrations of NaCl can act in combination with high pressures to further depress intracellular vitrification, highlighting the interplay between temperature, pressure, and ions in influencing the physical state of cells in natural environments. These results show that cells in subzero high-pressure environments can remain liquidous, and potentially metabolically active, and not merely vitrified and preserved. Additionally, our results provide considerations in the preparation of biological samples through high-pressure freezing for electron microscopy, particularly those associated with high concentrations of cryoprotectants.